A LEGAL ANALYSIS OF THE BALANCE SHEET. - Dohr, J. L. (The Accounting Review, 1928)
Abstract In connection with the accounting terms, assets, liabilities, and net worth, a word of caution is necessary. By definition, it is obvious that in any case the total asset minus the total liabilities is equal to the net worth. As a result of this method of portrayal, the balance sheet has often been completely misunderstood and the layman frequently asks why it is that assets and liabilities are always of equal amount. To explain, the accountant has upon occasion gone so far as to personalize the business as distinct from its owner, and the net worth is referred to as a liability of the business to its owner. This, of course, only leads to confusion and various attempts have been made to explain the situation more clearly. Thus it has been advocated that the term liabilities be abandoned and that there be substituted therefore the term equities. Under this plan all obligations of a business to creditors and others are termed equities and the net worth of the business is termed the equity of the proprietor.